Rice versus Shrimp Production in Thailand: Is There Really a Conflict? - Thamrong Mekhora; Laura M.J. McCann (My University, 2003)
Shrimp farming in Thailand has had disastrous effects on the environment in the past, which has prompted a government ban on shrimp production in inland areas. However, a new low-salinity shrimp farming system has developed that seems to have fewer disease and environmental problems than previous systems but competes with rice production for land and water resources. The present study found that shrimp farming exhibits increasing returns to scale and is much more profitable than rice farming, which offers opportunities for rice farmers to improve their incomes through diversification. No evidence was found for external environmental effects of shrimp production on rice production or vice versa. A total ban on shrimp production in rice farming areas does not seem justified, although further analysis on the environmental effects of this farming system is warranted.
Keywords: Shrimp farming; Social and Economic Development in India